Proteomics reveals different pathological processes of adipose tissue, liver, and skeletal muscle under insulin resistance. Issue 10 (1st March 2020) - Li, Yaqi; Ma, Quantao; Li, Pengfei; Wang, Jingkang; Wang, Min; Fan, Yuanyuan; Wang, Tieshan; Wang, Chunguo; Wang, Ting; Zhao, Baosheng
Abstract: Type 2 diabetes mellitus is the most common type of diabetes, and insulin resistance (IR) is its core pathological mechanism. Proteomics is an ingenious and promising Omics technology that can comprehensively describe the global protein expression profiling of body or specific tissue, and is widely applied to the study of molecular mechanisms of diseases. In this paper, we focused on insulin target organs: adipose tissue, liver, and skeletal muscle, and analyzed the different pathological processes of IR in these three tissues based on proteomics research. By literature studies, we proposed that the main pathological processes of IR among target organs were diverse, which showed unique characteristics and focuses. We further summarized the differential proteins in target organs which were verified to be related to IR, and discussed the proteins that may play key roles in the emphasized pathological processes, aiming at discovering potentially specific differential proteins of IR, and providing new ideas for pathological mechanism research of IR. Abstract : Our review of proteomics studies showed that the main pathological processes of insulin resistance (IR) among target organs were diverse and showed unique characteristics and focuses, which may be a part of the molecular mechanisms of the diverse phenotypes of the metabolic syndrome of the three target tissues under IR. We further summarized and discussed the differential proteins in target organs which were may play key roles in the emphasized pathological processes.